"Dude, that Sucks": Examining Scrum's Influence on Empathy in Student Teams. Issue 2 (3rd April 2021) - Friess, Erin; Lam, Chris
ABSTRACT: The role of empathy in student team collaborations in technical and professional communication has been understudied. In this mixed methods study, we assess how Scrum affects both student perceptions of empathy and student use of empathetic strategies. We found that students who used Scrum considered themselves to be no more empathetic than students who did not use Scrum. However, a discourse analysis revealed that students who used Scrum deployed significantly more empathetic strategies than students who did not use Scrum.